How is Performance Appraisal practices affected by Organizational Commitment in Yemeni Islamic Banks Using Subjective Norms as a Mediator? - Emam, Ali Salman; Ali, Gamal Abdualmajed; Oukil, Rabah; Sallem, Ramzi (Journal of Ecohumanism, 2024)
This study examined the influence of organizational commitment on Performance, and the level to which subjective norms plays a role in the relationship. The interrelationships between the variables were analyzed to develop a strategy for increased Performance Appraisal in the Yemeni Islamic banking. Because it will assist banks in developing a unique performance evaluation model if staff members are dedicated to carrying out their responsibilities in an excellent manner. This study used a social exchange theory to illustrate the study framework to link the relations between organizational commitment, Performance and subjective norms. This study relied on quantitative approaches. The study sample comprised of Yemeni Islamic banks’ employees. (400) questionnaires were distributed to employees, out of which 284 were retrieved and deemed usable for analysis, constituting a 65% rate of response. The Statistical Package for Social Science (SPSS) was employed to analyze data and test the proposed hypotheses. The findings showed that organizational commitment and Performance Appraisal in Yemen’s Islamic banks are significantly correlated. What’s more, this research showed that subjective norms play a big role as a mediator in the relationship between Performance Appraisal organizational commitment.